Amperometric biosensor for histamine determination. - Salleh, Abu Bakar; Abu Bakar, Fatimah; Wagiran, Rahman; Ching, Mai Keow; Lee, Yook Heng; Ahmad, Anuar; Mustaffa, Rosnin (2007)

(untitled)
There is provided by this invention a simple and rapid amperometric biosensor for determining the level of histamine in seafood or fish. The biosensor combines the technology of screen-printing with immobilized diamine oxidase as bioreceptor. In one embodiment of the present invention, the biosensor incorporates potassium hexacyanoferrate (III) as a mediator.